A practice-oriented mechanism of an integrated nlp conflict management model in construction projects - Makatora, Dmytro; Kubanov, Ruslan; Klymenko, Mykola (Khmelnytskyi National University (Ukraine), 2026)
Construction projects belong to the most complex and high-risk areas of managerial activity, where conflicts arise at almost all stages of implementation – from planning and coordination of technical solutions to execution of works and project commissioning. A high level of uncertainty, multilateral interaction among stakeholders, dependence on suppliers, and strict deadlines create conditions of constant tension and emotional strain. Traditional approaches to conflict management, based mainly on administrative or legal instruments, often prove insufficient, as they do not consider the psychological and communicative aspects of interaction. In this context, the use of neuro-linguistic programming (NLP) becomes particularly relevant, as it enables work with the behavioural, emotional, and cognitive factors of conflicts. The purpose of the study is to develop a practice-oriented mechanism of an integrated NLP conflict management model in construction projects. The methodological framework is based on systemic, communicative, and psychological approaches that combine the analysis of scientific sources, comparative analysis of traditional and modern methods, case studies, and modelling of managerial situations. The proposed model consists of three interrelated blocks: conflict prevention, conflict management, and conflict resolution. At the first level, techniques of rapport, calibration, and communication pattern analysis are applied, ensuring communication stability and early identification of risks. The second level includes reframing, behaviour modelling, and state management, which makes it possible to stop escalation and redirect interaction into a constructive channel. The third level is aimed at achieving mutually agreed solutions and restoring cooperation through the use of sensory language (VAK adaptations), the three perceptual positions, the Milton model, Interest Mapping, the win-win approach, and the Future Pacing technique. The results of the study confirm that the integration of NLP techniques into construction project management practice helps reduce the number of conflicts, shorten the time required for their resolution, increase the level of trust among participants, and ensure the stability of project implementation. The practical significance of the study lies in the development of recommendations for managers and executives of construction companies regarding the introduction of NLP methodologies into daily managerial activities. Thus, the proposed model is an innovative tool that combines psychological and communicative aspects of conflict management, promotes the development of a culture of trust and openness, and enhances the effectiveness of construction projects in modern conditions.
Keywords: neuro-linguistic programming (NLP); conflict management; construction projects; communication in management; rapport; calibration; reframing; project management; 005.8:005.334.2]:721.011